Eklsoftalmometri Penduduk Darah Iatimewa Yogyakarta - Mu'tasimbillah Ghozi Mu'tasimbillah Ghozi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
The normal position of the eyeball in the orbit is called euophthalmos. The enlargement of tissues inside the orbit will cause protrusion of the eyeball, which is called exophthalmos. Exophthalmos is one of the symptoms of some diseases either local or systemic.Exophthalmometry is a method of measuring the position of the eyeball in the orbit. Normal value of euophthalmos is 16 mm.Exophthalmometry among the population of Yogyakarta was done and discussed in this paper.Key Words: eyeball - orbit - euophthalmos exophthalmos - exophthalmometry